DEVELOPING CULTURE-BASED ENGLISH LEARNING MATERIAL FOR GRADE SEVEN OF JUNIOR HIGH SCHOOL IN BULELENG SUB-DISTRICT TO SUPPORT THE IMPLEMENTATION OF CURRICULUM 2013 - ., Luh Sri Damayanti; ., Prof. Dr.I Nyoman Adi Jaya Putra, MA; ., Drs.Gede Batan,MA (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
This research was aimed to design and develop culture-based English learning material for second semester of grade seven of junior high schools in Buleleng sub-district to support the implementation of curriculum 2013. This research was designed as research and development by following RnD model proposed by Peffers et.al (2007) as cited in Ellis and levy (2010) which consisted of six steps. The development of English learning material was in form of textbook. The development of English material was based on the need analysis. The data of need analysis were gained through the interview, questionnaires, and analysis the syllabus. Settings of this research were nine junior high schools in Buleleng sub-district. Balinese cultural values and character values in the textbook were integrated through the pictures, stories, dialogues, learning activities. Data were analyzed both qualitatively and quantitaviely.The quality of the textbook was assessed through expert judgment. Three aspects in the textbook were assessed through expert judgment form, namely content aspect, presentation aspect, and the aspect of integration of Balinese culture and character values. Based on the scores given by two experts, the quality of the textbook was categorized as excellent quality since the score given by expert 1 was 156 and expert 2 was 152. The reliability of the data was measured by using Alpha Cronbach’s coefficient. The result of the data analysis showed that α Cronbach’s coefficient was 0.77 and it was categorized as acceptable. In short, the developed culture-based English textbook has good quality and the data were reliable. Kata Kunci : Balinese culture-based learning material, English learning material, textbook, research and development, curriculum 2013 This research was aimed to design and develop culture-based English learning material for second semester of grade seven of junior high schools in Buleleng sub-district to support the implementation of curriculum 2013. This research was designed as research and development by following RnD model proposed by Peffers et.al (2007) as cited in Ellis and levy (2010) which consisted of six steps. The development of English learning material was in form of textbook. The development of English material was based on the need analysis. The data of need analysis were gained through the interview, questionnaires, and analysis the syllabus. Settings of this research were nine junior high schools in Buleleng sub-district. Balinese cultural values and character values in the textbook were integrated through the pictures, stories, dialogues, learning activities. Data were analyzed both qualitatively and quantitaviely.The quality of the textbook was assessed through expert judgment. Three aspects in the textbook were assessed through expert judgment form, namely content aspect, presentation aspect, and the aspect of integration of Balinese culture and character values. Based on the scores given by two experts, the quality of the textbook was categorized as excellent quality since the score given by expert 1 was 156 and expert 2 was 152. The reliability of the data was measured by using Alpha Cronbach’s coefficient. The result of the data analysis showed that α Cronbach’s coefficient was 0.77 and it was categorized as acceptable. In short, the developed culture-based English textbook has good quality and the data were reliable. keyword : Balinese culture-based learning material, English learning material, textbook, research and development, curriculum 2013